2012
DOI: 10.1080/10942911003687256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooking on the Bioactivity of Lotus Roots and White Onions

Abstract: Bioactive compounds and antioxidant potentials were determined in fresh lotus roots and subjected to boiling for different periods of time (10, 20, 40, and 60 min). The obtained results were compared with the same indices in fresh and boiled white onions. It was found that fresh vegetables contained higher quantities of bioactive compounds than those boiled for 10 min, and these indices were significantly higher in fresh white onions than in fresh lotus roots (P < 0.05). Polyphenols (mg GAE/g) were 3.65 ± 0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…In the conducted research, a decrease in the content of total polyphenols, flavonoids, and flavanols was found during the extended time of thermal treatment. The observed trends are confirmed by studies by other authors who suggest that technological treatments may change the phenolic compounds contained in garlic or other plants from the Alliaceae family [40,41]. Blanching for 90 s (G90s) and microwaving raw (GF micro) or blanched garlic (G90s micro) used in the present study led to the lowest loss of bioactive compounds, and the results obtained for heat-treated garlic were comparable with the results of other authors [42].…”
Section: Samplesupporting
confidence: 91%
See 2 more Smart Citations
“…In the conducted research, a decrease in the content of total polyphenols, flavonoids, and flavanols was found during the extended time of thermal treatment. The observed trends are confirmed by studies by other authors who suggest that technological treatments may change the phenolic compounds contained in garlic or other plants from the Alliaceae family [40,41]. Blanching for 90 s (G90s) and microwaving raw (GF micro) or blanched garlic (G90s micro) used in the present study led to the lowest loss of bioactive compounds, and the results obtained for heat-treated garlic were comparable with the results of other authors [42].…”
Section: Samplesupporting
confidence: 91%
“…In turn, losses of biologically active ingredients under the influence of heating are related, among others, to with the rate of heat transfer into tissues. Heating in water causes the effect of temperature in the entire volume of the material; therefore, it leads to greater losses than heating in air or steam [38][39][40][41], as demonstrated in the present study.…”
Section: Lipid Profile In Rats Supplemented With Freeze-dried Fresh A...supporting
confidence: 64%
See 1 more Smart Citation
“…Onion, like garlic, contains inhibitors of lipoxygenase and cyclooxygenase (enzymes that produce inflammatory hormones-prostaglandins and thromboxanes), which, together with the other biologically active compounds contained in it, exert an anti-inflammatory effect in the body [49]. Onions are rich in many biologically active compounds that reduce the risk factors for cardiovascular disease [5,6,8,10,11,22,[50][51][52]. Epidemiological studies show that there is a strong association between a diet high in onion and a reduction in the risk of mortality from ischemic heart disease [3].…”
Section: Introductionmentioning
confidence: 99%